Model-based fault localization in bottling plants. Issue 1 (January 2015) - Voigt, Tobias; Flad, Stefan; Struss, Peter
Highlights We created a customizable solution for automatic fault diagnosis in bottling plants. The model-based approach allows the generation of individual diagnosis solutions. New validated models for all relevant plant components were developed. The diagnosis solution was tested in practical scale and judged as a useful tool. Up to 87.1% of compliant diagnosis results were obtained.